Laboratory mice engrafted with natural gut microbiota possess a wildling-like phenotype - Solveig Runge; Silvia von Zedtwitz; Alexander M. Maucher; Philipp Bruno; Lisa Osbelt; Bei Zhao; Anne M. Gernand; Till R. Lesker; Katja Gräwe; Manuel Rogg; Christoph Schell; Melanie Boerries; et al. (Nature Communications)
Abstract Conventional laboratory mice housed under specific pathogen-free (SPF) conditions are the standard model in biomedical research. However, in recent years, many rodent-based studies have been deemed irreproducible, raising questions about the suitability of mice as model organisms. Emerging evidence indicates that variability in SPF microbiota plays a significant role in data inconsistencies across laboratories. Although efforts have been made to standardize microbiota, existing microbial consortia lack the complexity and resilience necessary to replicate interactions in free-living mammals. We present a robust, feasible and standardizable approach for transplanting natural gut microbiota from wildlings into laboratory mice. Following engraftment, these TXwildlings adopt a structural and functional wildling-like microbiota and host physiology toward a more mature immune system, with characteristics similar to those of adult humans. We anticipate that adopting wild mouse-derived microbiota as standard for laboratory mouse models will improve the reproducibility and generalizability of basic and preclinical biomedical research.